Examining the Impact of Jail Sanctions on Recidivism for Domestic Violence Probationers - Romain Dagenhardt, Danielle M. (Journal of interpersonal violence, 2023)
There has been a growth of domestic violence courts aimed at increasing offender accountability and victim safety. Although research has examined the effectiveness of these courts compared to typical court processing on recidivism, little is known about the mechanism of judicial accountability. Specifically, judicial review hearings, in which judges have discretion on whether and how to sanction for noncompliance, are common in these courts. This study examines whether incarceration sanctions for noncompliance affect recidivism among a sample of 347 probation review hearings in a Midwestern domestic violence court. Using logistic regression and survival analysis, we find that jail sanctions do not impact likelihood of recidivating but do result in significantly shorter periods of time until recidivating. The findings also signify the importance of addressing substance abuse issues in the prevention of recidivism. Further implications of the findings are discussed.